2023
DOI: 10.1021/acs.jafc.3c01270
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Novel Pyrazoloquinazoline on Diamondback Moth (Plutella xylostella) Ligand-Gated Chloride Channels

Abstract: In our previous study, a series of novel pyrazoloquinazolines were synthesized. Pyrazoloquinazoline 5a showed high insecticidal activity against the diamondback moth (Plutella xylostella) and no cross-resistance to fipronil. Patch clamp electrophysiology performed on P. xylostella pupae brains and two-electrode voltage clamp electrophysiology performed on Xenopus Laevis oocytes indicated that 5a might act on the ionotropic γ-aminobutyric acid (GABA) receptor (GABAR) and glutamate-gated chloride channel (GluCl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…xylostella have developed a strong resistance, even cross-resistance, against traditional insecticides. Meanwhile, the health risks and eco-unfriendly effects also appeared. The increment of environmental preoccupations and the growing demands for more high-yielding and healthy food call for green alternatives to resistant insecticides. Hopefully, plant secondary metabolites, defended against chewing herbivores in the process of the ongoing evolution of plant–pest interactions, are the important sources for the discovery of novel pesticide candidates. ,, Caffeoyl and flavonoid derivatives, as widespread secondary metabolites in various plants, exhibited many bioactivities, including anti-inflammation, antiviral, antioxidant, antibacterial, and anticancer, while their bioactivities in agriculture were reported scarcely. …”
Section: Introductionmentioning
confidence: 99%
“…xylostella have developed a strong resistance, even cross-resistance, against traditional insecticides. Meanwhile, the health risks and eco-unfriendly effects also appeared. The increment of environmental preoccupations and the growing demands for more high-yielding and healthy food call for green alternatives to resistant insecticides. Hopefully, plant secondary metabolites, defended against chewing herbivores in the process of the ongoing evolution of plant–pest interactions, are the important sources for the discovery of novel pesticide candidates. ,, Caffeoyl and flavonoid derivatives, as widespread secondary metabolites in various plants, exhibited many bioactivities, including anti-inflammation, antiviral, antioxidant, antibacterial, and anticancer, while their bioactivities in agriculture were reported scarcely. …”
Section: Introductionmentioning
confidence: 99%
“…In China, the management and crop losses are estimated to be about $0.77 billion per year . The abuse of conventional pesticides not only has harmful effects on the environment but also leads to the development of drug-resistant populations of P. xylostella . Azadirachtin A, found in plants, is used worldwide in agriculture and pest management for its insecticidal properties. Its popular application indicated that natural insecticides have the potential to be practical substitutes for synthetic pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Pyraquinil (Pyr), containing the skeleton of 4,5-dihydropyrazolo­[1,5- a ]­quinazoline-fused heterocycle, is a novel insecticide recently developed by our research team. , Being the first 4,5-dihydropyrazolo­[1,5- a ]­quinazoline insecticide, pyraquinil elicits its bioactivity by interference with the passage of chloride ions through the γ-aminobutyric acid (GABA) receptor of pests. Hence, pyraquinil could act as a new type of ligand-gated chloride channel (LGCC) antagonist. , Pyraquinil has the advantages of low dosage and high efficacy, and it can effectively control a variety of Lepidoptera pests. , The insecticidal activity of pyraquinil is 64-fold better than that of fipronil against the field-resistant populations of diamondback moth (Plutella xylostella), which is one of the most destructive insects of cruciferous plants. Furthermore, pyraquinil shows almost no cross-resistance to fipronil against P.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the potential toxicity and growing resistance of fipronil, pyraquinil is likely to have a great future development and is expected to be a promising alternative to fipronil. , This insecticide is currently in the registration process in China, and has also been patented in Japan, Brazil, the United States, and the European Union . In consideration of the long persistence, negative impact on the ecosystem, and toxic TPs of the traditional GABA receptor antagonist insecticides (such as fipronil), it was essential to carry out research on the environmental behavior and ecological toxicity of pyraquinil as well as its TPs. However, as a new pesticide, previous studies on pyraquinil were mainly focused on its synthesis method, insecticidal activity, , mode of action, , and toxicokinetics . To date, the only existing research related to environmental behavior has been the establishment of the stereoselective analytical methods of pyraquinil isomers in vegetables .…”
Section: Introductionmentioning
confidence: 99%